Urban hopes : made in China by Steven Holl - Holl, Steven; Kumpusch, Christoph a. (Zürich : Lars Müller, 2014)
In content and format the book reflects such juxtaposition, featuring images and graphic documentation of Steven Holl's recent works realized in China alongside critiques and analyses by a new generation of theorists.
Oceanic / Balthasar Holz -- Introduction / Steven Holl -- Urban manifestos -- Histories -- Tianjin Museums (Tianjin, China) -- Horizontal skyscraper (Vanke Center, Shenzhen, China) -- Sliced porosity block (Chengdu, China) -- Linked hybrid (Beijing, China) -- Tropical porosity plan (Dongguan, China) -- Conclusion: irrationale / Christoph a. Kumpusch.
ARC
Keywords: Holl, Steven -- Pictorial works; Architecture -- China -- History -- 20th century -- Pictorial works; Architecture, Modern -- 20th century -- Pictorial works; Architectural drawing; Architectural design; Architektur; China